On the development of an automatic voice pleasantness classiﬁcation and intensity estimation system - Coelho, Luís (2014)
In the last few years, the number of systems and devices that use voice based interaction has grown signiﬁcantly. For a continued use of these systems, the interface must be reliable and pleasant in order to provide an optimal user experience. However there are currently very few studies that try to evaluate how pleasant is a voice from a perceptual point of view when the ﬁnal application is a speech based interface. In this paper we present an objective deﬁnition for voice pleasantness based on the composition of a representative feature subset and a new automatic voice pleasantness classiﬁcation and intensity estimation system. Our study is based on a database composed by European Portuguese female voices but the methodology can be extended to male voices or to other languages. In the objective performance evaluation the system achieved a 9.1% error rate for voice pleasantness classiﬁcation and a 15.7% error rate for voice pleasantness intensity estimation.